Crystal engineering of a hybrid metal–organic host framework and its single-crystal-to-single-crystal guest exchange using second sphere coordination. Issue 13 (8th March 2016) - Li, Lei; Tong, Jian; Guo, Fang; Martí-Rujas, Javier
Abstract : A robust metal–organic adduct displaying 1D channels has been prepared using second sphere interactions through charge-assisted hydrogen bonds. The solid can exchange guest molecules via SCSC reactions and shows guest selectivity depending on the channel size. Abstract : By means of crystal engineering principles, a new second sphere coordination adduct has been synthesized using charge-assisted hydrogen bonds and self-assembling [CdBr6 ] 4− and Br − anions with a V-shaped diprotonated cation. The second sphere adduct is homologous to a copper network, forms a host framework with 1D channels and has good thermal stability (200 °C) upon guest release. The [CdBr6 ] 4− anion shows Jahn–Teller distortion as revealed by X-ray crystallography. Guest exchange via a single-crystal-to-single-crystal manner is reported. The guest behavior is different to that of the homologous Cu adduct due to the pore size effect.